Determination of Gas Potential and Urban Solid Waste Management in Elazığ - Argunhan, Zeki; Yücel, Halit Lutfi; Yıldız, Cengiz (Bitlis Eren Üniversitesi, 2023)
Solid wastes make the most important environmental problems caused by human all over the world. In recent years, the amount of solid waste has been increasing in Elazig day by day with rise in the population and industrialization. The solid waste managing systems contain the methods such as proper storage, recycling, processing the solid waste by means of biological methods (compost), and disposal with thermal methods (burning, gasification, and pyrolysis). Of these methods, the proper storage is the most common one in Elazig. By time, using up the oxygen within the wastes stored in the proper fields, the storage gas occurs as a result the decay without oxygen (anaerobic) with the help of anaerobic bacteria proliferate in this environment. In this study, solid waste disposal methods have been investigated for storage gas by giving Elazig example.
Keywords: Energy Generation; Conversion and Storage (Excl. Chemical and Electrical); Enerji Üretimi; Dönüşüm ve Depolama (Kimyasal ve Elektiksel hariç)